Performance enhancement of a terahertz patch antenna with metamaterials for 6G and biomedical applications - Younes, Siraj; Alaoui, Kaoutar Saidi; Foshi, Jaouad (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
This paper introduces a novel approach for enhancing the performance of a terahertz (THz) patch antenna through the integration of metamaterials (MTM). The proposed design features a rectangular slotted patch antenna with a partial ground structure (DGS) that operates at 3.56 THz. The radiating element is situated on a substrate composed of silicon dioxide (SiO2) with a dielectric of 4 and a thickness of 2 µm. The proposed MTM is a 6×5 elements with a FR4 substrate characterized by a dielectric of 4.2 and a thickness of 2 µm. The MTM is integrated beneath the antenna as a strategic technique to enhance its performance. The results confirm the significant impact of this integration. The MTM improves impedance matching and makes the antenna more directional. Consequently, the reflection coefficient is improved from -18.06 dB to -52.50 dB, the gain is increased from 1.72 dB to 3.49 dB, and the directivity also is enhanced from 3.69 dB to 5.10 dB. All results were obtained using HFSS software.